Changing role of nursing cadre under emerging zoonotic diseases - Divya Aggarwal; Sumant Swain; Anandhi Ramachandran; Vijit Chaturvedi; Sanjiv Kumar (Wolters Kluwer Medknow Publications, 2020)
With the launch of new Government of India's initiative Ayushman bharat that envisages conversion of all subcenters into health and wellness centers, the role of nursing professionals in primary health care will be undergoing paradigm shift. Nurses are approximately two-third of the population of health workforce in India. Nurses' scope of work has widened with additional roles and responsibilities due to shift in the pattern of burden of diseases. The emergence of zoonotic infectious diseases has further enlarged their responsibilities. The main areas, which need attention, are development of nursing workforce, selection and recruitment, placement as per specialization, and preservice and in-service training related to zoonotic surveillance. This article attempts to discuss the role of nurses under emerging zoonotic disease infections.